Perlindungan Hukum Hak Awak Kapal Dalam Pelaksanaan Perjanjian Kerja Laut - Thomas Narpati Hendrawan; Achmad Fitrian; Gatut Hendro Tri Widodo (Jurnal Penelitian Hukum Legalitas, 2023)
The shipping sector is one of the vital sectors in the transportation of people and goods, so in the implementation of shipping activities, workers who work on ships are called as Ship's Crew (ABK). According to Law Number 17 of 2008 on Shipping, crew members are ship’s crew members other than masters, what is meant by crew members are people who work or are employed on a ship by the ship’s owner or operator of the ship to carry out tasks on board according to their position listed in the seafarer’s book (monsterrol). Problems related to legal protection of the rights of crew members in implementing seafarer employment agreements are mostly disputes about termination while the employer does not provide severance pay due to the legal principle that applies to seafarer employment agreements is referring to specific legal principle, namely lex specialis derogate lex generalis. The results of the study show that the legal basis for making maritime labor agreements in principle refers to Book II Chapter 4 of the Indonesian Commercial Code concerning Seafarer Employment Agreements. Nevertheless, the provisions of seafarer employment agreements in the Indonesian Commercial Code refer further to the provisions of employment agreements in Chapter 7A Book III of the Indonesian Civil Code, furthermore, in the procedure for seafarer employment agreement, seafarer employment agreements must fulfil legal requirements such as work agreements in general, but there is a slight difference in that work agreements generally only have two subjects involved in a work agreement. In the making of a seafarer employment agreements between the employer and the ship's crew must be made before the Syahbandar and legal protection for the crew is regulated in the seafarer employment agreements where the Government Regulation on the Seamanship that the seafarer employment agreements requires minimum wages, leave, welfare, safety and other than that, if there is an industrial relations dispute, it can resolve through the bipartite and tripartite phase.